Pengaruh Kepemimpinan Kepala Sekolah dan Budaya Sekolah terhadap Disiplin Kerja Guru SMP Negeri di Kecamatan Sembawa Kabupaten Banyuasin - Septiana Septiana; Happy Fitria; Ahmad Wahidy (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the influence of principal leadership and school culture on teacher discipline in public junior high schools (SMP Negeri) in Sembawa District, Banyuasin Regency. Teacher discipline is an important factor in supporting the effectiveness of the learning process and achieving educational goals. Therefore, understanding the factors that contribute to teacher discipline is essential for improving school performance. This study employed a quantitative research method with a purposive sampling technique. Data were collected through the distribution of questionnaires consisting of 66 statement items measured using a five-point Likert scale. The collected data were analyzed using statistical techniques to determine both partial and simultaneous effects of the independent variables on teacher discipline. The results indicate that principal leadership has a positive and significant partial effect on teacher discipline, as evidenced by a t-value of 5.127, which is greater than the t-table value of 1.9809. School culture also has a positive and significant partial effect on teacher discipline, with a t-value of 7.244 exceeding the t-table value of 1.9809. Furthermore, principal leadership and school culture simultaneously have a positive and significant effect on teacher discipline, as indicated by an F-value of 34.152, which is greater than the F-table value of 3.07. These findings suggest that strengthening principal leadership and fostering a positive school culture can significantly improve teacher discipline.